PENGEMBANGAN BAHAN AJAR LEMBAR KERJA SISWA BANGUN DATAR DAN BANGUN RUANG DENGAN MENGGUNAKAN POLA BARISAN - Anika Musayadah; Salsabila Rizki Rofikoh; Naila Ulfatusy Syarifah; Muh Syauqi Malik (Prodi Pendidikan Guru Madrasah Ibtidaiyah STAIN Teungku Dirundeng Meulaboh, 2023)
Mathematics is a learning that connects concepts and mathematical structures such as in flat building and space building materials. In delivering learning materials, a teacher will use teaching materials. Teaching materials are materials compiled by teachers to achieve learning objectives. The right teaching material for flat building and building space materials in class II is the Student Worksheet. With the Student Worksheet, students can increase their understanding of the material they are studying because the teaching material is designed with many pictures, practice questions, and colors. So that learning can run effectively . The method used in this study is the library method by making books, articles, journals, as references. From the research conducted, it was obtained that the teaching materials of the Student Worksheets on the material of building flat and building spaces using row patterns can be used in students of grade II Elementary School.